Pengaruh Variabel Makroekonomi Terhadap Index Harga Saham Syariah - Annisa Masruri Zaimsyah; Alvira ‘Aina Ayun; Khofidlotur Rofi’ah; Sri Herianingrum (Jurnal Ekonomi, 2020)
The purpose of this paper is to investigate macroeconomic indicators that affect sharia stock prices in Asia Muslim majority countries. This research used inflation, interest rates and exchange rate in Indonesia, Malaysia, Saudi Arabia and Bangladesh. This research use data panels and multiple linear regression analyses using the Ordinary Least Square (OLS) method as a parameter. The results show inflation and exchange rates have no effect on sharia stock prices, while interest rates have a negative effect. Implications for investors who want to invest in stocks to attention macroeconomic variables that affect the movement of stock price, information that related macroeconomic conditions, information that predicts fluctuation stock price. This study has limitations only focus on four countries in Asia and only use three most dominant macro variables. Future research can improve other macroeconomic variables such as world oil prices and gross domestic income. The novelty of this research examines the Sharia stock market in Muslim majority countries in Asia.